Kecelakaan Kerja pada Pemulung di Tempat Pembuangan Akhir Sumompo Kota Manado - Asterlita Ryane Wenas; Diana Vanda Daturada Doda; Jehosua Sinolungan (STIKes Payung Negeri Pekanbaru, 2021)
Scavengers were the one of the informal workers who work in the landfill. Scavengers have a high risk of having work accidents. The purpose of this study was to determine the prevalence of work accidents and factors related to work accidents among scavengers at the Sumompo landfill Manado city. This was a correlational analytic research with a cross-sectional approach. This research was conducted at the Sumompo landfill Manado city in January-February 2021. The respondents in this research were 110 scavengers. The research variables consisted of the independent variable (knowledge of personal protective equipment/ PPE, the action to use of PPE and the work time period) and the dependent variable (work accidents). The data obtained were analyzed by univariate and bivariate. The results of this research showed that the respondents are most widely distributed on good knowledge (56.4%), bad actions (60%), long work time period (74.5%) and have work accidents (73.6%). The results of the bivariate analysis showed that the action of using PPE was correlated to work accidents (p = 0.024). The results of the analysis show that scavengers who have bad actions to use PPE are more at risk of having work accidents when compared to scavengers who have good actions to use PPE. That can be concluded that the prevalence of work accidents in scavengers is 73.6% and the action of using PPE was a factor associated with work accidents.